FAMILY EDUCATION STRATEGIES IN CARING FOR CHILDREN WITH CONGENITAL ADRENAL HYPERPLASIA (CAH): A LITERATURE REVIEW - Meira Erawati; Maya Ajeng Lestari (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2020)
Families having children with congenital adrenal hyperplasia (CAH) may have low knowledge and awareness in some aspects of CAH management. Information and education regarding caring for children with CAH is essential for families so that they can provide proper care and treatment to their children. This study aims to describe the strategy of family education about caring for children with CAH from the existing literature. A literature review was performed by investigating relevant studies from online databases of Google Scholar, Science Direct, PubMed, and BioMed Central. Keywords of “education” and “children” and “congenital adrenal hyperplasia” and “family or parents” were used in searching the data. The results of the review showed various strategies that can be applied to provide education to families, especially parents. These strategies include providing detailed care instructions about adrenal crisis management, encouraging families/ parents to use positive and useful coping strategies, increasing knowledge and awareness on the use of medical alert IDs, providing Psychosocial Education Program (PEP), increasing nurses’ knowledge and comfort in providing education to families, and suggestions for improving the provision of family education. The provision of education to families or parents having children with CAH should consider some individual aspects such as emotional states, health literacy, learning styles, the amount of information, and knowledge assessment of each family/parent.